The Effect of Competitive Strategy, Resource Capability, and Market Orientation on SMEs Performance - Mislan Sihite; Gusti Marliani; Indra Darmawan; Muhammad Abduh (Malaqbi Publisher, 2026)
The Effect of Competitive Strategy, Resource Capability, and Market Orientation on SMEs Performance